Single Flux Quantum-Based Digital Control of Superconducting Qubits in a Multichip Module - C.H. Liu; A. Ballard; D. Olaya; D.R. Schmidt; J. Biesecker; T. Lucas; J. Ullom; S. Patel; O. Rafferty; A. Opremcak; K. Dodge; V. Iaia; et al. (PRX Quantum, 2023)
Single flux quantum (SFQ) digital logic has been proposed for the scalable control of next-generation superconducting-qubit arrays. In the initial implementation, SFQ-based gate fidelity was limited by quasiparticle (QP) poisoning induced by the dissipative on-chip SFQ driver circuit. In this work, we introduce a multichip-module architecture to suppress phonon-mediated QP poisoning. Here, the SFQ elements and qubits are fabricated on separate chips that are joined with In-bump bonds. We use interleaved randomized benchmarking to characterize the fidelity of SFQ-based gates and we demonstrate an error per Clifford gate of 1.2(1)%, an order-of-magnitude reduction over the gate error achieved in the initial realization of SFQ-based qubit control. We use purity benchmarking to quantify the contribution of incoherent error at 0.96(2)%; we attribute this error to photon-mediated QP poisoning mediated by the resonant millimeter-wave antenna modes of the qubit and SFQ-qubit coupler. We anticipate that a straightforward redesign of the SFQ driver circuit to limit the bandwidth of the SFQ pulses will eliminate this source of infidelity, allowing SFQ-based gates with error approaching approximate known theoretical limits, of order 0.1% for resonant sequences and 0.01% for more complex pulse sequences involving variable pulse-to-pulse separation.